Putative Prevention of XML Injection Against Myocardial Ischemia Is Mediated by PKC and PLA2 Proteins - Jin, Ling; Yin, Qianqian; Mao, Yiqing; Gao, Yuanxu; Han, Qing; Mei, Ruisi; Xue, Lixiang; Tan, Huanran; Li, Hui (Frontiers in Cell and Developmental Biology, 2022)
Background: Xinmailong (XML) injection is a CFDA approved traditional chinese medicine with clinical value of heart failure treatment. The present investigation was aimed to evaluate the potential protective roles of this injection on myocardial ischemia, as well as the underlying molecular mechanism. Methods: In our study, we selected two models of myocardial ischemia rats. Rats were randomly divided into six groups, with saline or XML administrated 4days before ischemia model establishment. ECG of different time intervals and biochemical parameters of end-point were measured. The potential mechanisms of protective role of XML were explored using system pharmacology and molecular biology approaches. Results: myocardial ischemia rats demonstrated abnormal ECG and serum levels of cTnT. Pretreatment with XML significantly attenuated these damages, especially the medium does. GO and KEGG analysis revealed that the 90 putative target genes were associated with pathways of fatty acid absorption/metabolism, inflammation, RAAS and vascular smooth muscle. Further network pharmacology method identified five main chemical ingredients and potential targets of XML injection for myocardial ischemia. Mechanically, the beneficial effect of XML injection was mediated by the reactive oxygen species (ROS) inhibition and inflammation attenuation via regulating the expression levels of targets of PKC and PLA2. Conclusion: These findings indicate that XML exerts protective effects against myocardial injury, with attenuated ROS production, apoptosis and inflammation. Therefore, we spectulate that XML maybe an alternative supplementary therapeutic agent for myocardial ischemia prevention.